Tanggung Gugat Pengelola Statuter OJK Terhadap Kerugian Nasabah Atas Penundaan Pembayaran Klaim Asuransi Yang Sudah Jatuh Tempo Ditinjau Dari Undang–Undang Nomor 40 Tahun 2014 Tentang Perasuransian - Melinda Christiani; Yoan Nursari Simanjuntak; Irta Windra Syahrial (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This article raises a case regarding the actions of OJK statutory managers who in carrying out their functions, duties and authorities do not meet the provisions of the legislation, namely Article 62 paragraph (2) of the Insurance Law. The statutory provisions are not fulfilled because the OJK statutory manager in carrying out his functions, duties, and authorities is not in accordance with the statutory manager's duties as regulated in Article 62 paragraph (2) of the Insurance Law, but the actions of the OJK statutory manager do not result in losses for customers for delaying payments. insurance claims that are past due. The actions of the OJK statutory manager in carrying out their functions, duties, and authorities that violate the provisions of the legislation cannot be considered as an unlawful act as regulated in Article 1365 of the Civil Code where all elements of unlawful acts are not fulfilled. Based on Article 64 of the Insurance Law in conjunction with Article 1365 of the Civil Code, statutory managers are not obliged to be responsible for their unlawful acts. Keywords : Insurance Agreement, Statutory Manager, Tort, Liability